Analysis of the influence of work motivation, discipline and work culture on employee Performance CV. Roda Jati Kabupaten Demak - Dinia Restuningtyas; Artha Febriana (E-Bisnis : Jurnal Ilmiah Ekonomi dan Bisnis, 2019)
The research objectives are to analyzing the impact of work motivation, work discipline, and work culture on employee performance. CV. Roda Jati The research method used is a quantitative type with an explanatory design. The research subjects were all employees of CV. Roda Jati, totaling 57 people. The method of collecting power used was observation, documents, and questionnaires. The results of the study concluded that: 1) work motivation has a positive and significant effect on employee performance by 0.324 or 32.4%; 2) work discipline has a positive and significant effect on employee performance by 0.326 or 32.6%; 3) work culture has a positive and significant influence on employee performance by 0.314 or 31.4%; and 4) work motivation, work discipline, and culture have a positive and significant impact on employee performance CV. Roda Jati amounted to 0.321 or 32.1%.